2012
DOI: 10.1111/echo.12003
|View full text |Cite
|
Sign up to set email alerts
|

Does Chronic Atrial Fibrillation Induce Cardiac Remodeling?

Abstract: These findings demonstrate that in patients with CAF structural and functional cardiac changes occur. Patients with CAF as opposed to both normal subjects and patients with PAF have larger left atria and reduced systolic and diastolic left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Electric remodeling contributes to several clinically important phenomena, including early AF recurrence after cardioversion, progressive drug resistance of long-lasting AF, and progression from paroxysmal to more persistent forms. [6][7][8][9][10] There are several experimental evidences of antifibrillatory and antifibrotic effects of ACEI/ARBs probably by downregulating MAPK or ERK1/ERK2 expression and reducing collagenase activity. Currently, Kv1.5 potassium channel has been considered as an important molecular target for the treatment of AF because the atrial but not ventricular action potential duration could be prolonged selectively by inhibition of Kv1.5.…”
Section: Benefits and Possible Mechanisms Of Ras Blockade Therapy On mentioning
confidence: 99%
See 1 more Smart Citation
“…Electric remodeling contributes to several clinically important phenomena, including early AF recurrence after cardioversion, progressive drug resistance of long-lasting AF, and progression from paroxysmal to more persistent forms. [6][7][8][9][10] There are several experimental evidences of antifibrillatory and antifibrotic effects of ACEI/ARBs probably by downregulating MAPK or ERK1/ERK2 expression and reducing collagenase activity. Currently, Kv1.5 potassium channel has been considered as an important molecular target for the treatment of AF because the atrial but not ventricular action potential duration could be prolonged selectively by inhibition of Kv1.5.…”
Section: Benefits and Possible Mechanisms Of Ras Blockade Therapy On mentioning
confidence: 99%
“…1 However, current treatment strategies are still far from optimal. Structural remodeling, [6][7][8][9] particularly fibrosis caused by the arrhythmia itself or progression of underlying heart diseases, involves evolution from paroxysmal to persistent to permanent AF. [2][3][4] Recent evidences suggest that the pathogenesis of AF is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that patients with AF, as opposed to normal subjects, have larger left atria and reduced systolic and diastolic left ventricular function. 6 Vecih Oduncu, MD Cardiology Clinic Fatih Medical Park Hospital Fatih, Istanbul, Turkey…”
Section: To the Editormentioning
confidence: 99%
“…The heart pumps blood through the atria and ventricles, allowing the body to transport oxygenated blood to the rest of the body and deoxygenated blood to the lungs (Heart and Stroke Foundation, 2014). During atrial fibrillation, the electrical activity is triggered from many different areas of the atria and causes fibrillation, causing the atria to inadequately empty of blood (Cottrell, 2012;Fuchs et al, 2012). This pooling of blood in the atria along with turbulent flow, may in turn cause embolus formation, increasing the risk for stroke and atrial enlargement (Cotrell, 2012).…”
Section: The Pathophysiology and Management Of Afmentioning
confidence: 99%
“…AF was once considered a benign condition, but is now seen as a significant public health issue as a result of the profound impact upon mortality and morbidity. For example, AF can give rise to cardiac failure, enlargement of the left atrium and stroke (Fuchs et al, 2012). Ischemic stroke is of particular concern, with AF causing a three to five-fold increase in the risk for stroke and accounting for over twenty percent of all ischemic strokes (Kamel et al, 2016).…”
mentioning
confidence: 99%